Reinforced concrete building design project and project based learning: case study / Ahmad Faris Ahmad Nizam - Ahmad Nizam, Ahmad Faris (2022)
In conclusion, the design work for each of the structure elements has been succeed. In order to complete the task, we need to take consideration of some of the parameter such as shear, moment, deflection and last but not least the cracking. All of the proposed design has been analysed one after one in order to get the actual value. All of the proposed value has passed all the checking such as bending check and cracking check. All of the checking is required in order to design a structure that is stable, and rigid structure with a great and adequate strength. The structure needs to be strong enough in order to cater the load that come from the structure itself and the user soon. All the parameter has been obtained by assumption and analysis. The analysis will help to design the structure elements as it will show us the load that need to be cater by the structure element. Most of them will have to cater some loading from other elements such as beam, column, and pad footing. So, it is really important for us to do the analysis right before doing the design.